QUARTER OF A CENTURY IN THE LOOKING FOR OPTIMAL WAYS TO PREVENT NONINFECTIOUS DISEASES AND NEW TASKS FUTURE (TO THE 25TH ANNIVERSARY OF THE STATE RESEARCH CENTER FOR PREVENTIVE MEDICINE FOUNDING) (Столичная издательская компания, 2015)
.